LINE FOLLOWING ROBOT WITH HIGH RADIATION MATERIAL DETECTION CAPABILITY (FUDMA JOURNAL OF SCIENCES, 2021)
Advancement in technology have led to a rapid development in the design and manufacturing of robots, enabling them to provide human capabilities without the inherent shortcoming associated with human capabilities; such as boredom, fear, inefficiency etc. A mobile robot that can sense and observe the line drawn on the floor is the Line Follower Robot. The direction is usually predefined and can be either visible on a white surface with a high contrast colour like a black line or invisible like a magnetic field. Hence, with its Infrared Ray (IR) sensors mounted under the robot, this sort of robot can feel the line. Then, the information is conveyed by specific transition buses to the processor. The processor will determine the right commands and then send them to the driver, and the line follower robot will then follow the direction. Therefore, this paper focuses on the design of a mobile line following robot for detecting the high radiation level of a sample farmland and display on a 7-segment display by the aid of sensors to navigate through grid. The mobile line following robot must move through the squares and detect the high radiation levels and at the end provides us with information on the number of squares and detected high radiation levels. The robot's area of operation is limited to six squares each of dimension 60cmÃ—60 cm. Silver coloured square spots with dimensions of 5 cm by 5 cm made of foil paper are used to indicate a high radiation level
Keywords: Mobile Line Following Robot, Farmland, LDR Sensors, Infrared Ray, 7-Segment Display.